Capacity building and enhancing knowledge of the healthcare providers on inappropriate practices and dispensing of antimicrobials - Mubashir Hanif; Nawal Naeem; Shehzad Ali Khan; Ramesh Kumar; Sheraz Ahmed Khan; Mumtaz Ali Khan (Journal of the Pakistan Medical Association, 2024)
This paper reports on the training programme, aimed forhealthcare providers on the concepts of antimicrobialresistance (AMR) and build their understanding andknowledge on the causes and factors contributing to theAMR hence reducing the burden on the healthcaresystems. A team of experts developed the curriculum andteaching material. A 2-day training workshop wasconducted which included the pre- and post-knowledgeassessment of the participants on AMR. Four hundredfrontline healthcare workers (HCWs) from public andprivate hospitals were enrolled for the training. Threetypes of educational material were produced and used; aguidance booklet, documentaries on AMR, and a set ofPowerPoint presentations to explain the AMR and its linkwith one-health and overall importance. Participants’knowledge increased from 60 to 90 percentage pointsafter the training. Study concluded that the knowledgeon AMR among HCWs would positively improve theirprescribing and dispensing practices. Keywords: Stewardship, One-health, AMR, infections,microbes.